2013
DOI: 10.1111/jcpp.12168
|View full text |Cite
|
Sign up to set email alerts
|

Associations between birth weight and attention‐deficit/hyperactivity disorder symptom severity: indirect effects via primary neuropsychological functions

Abstract: Background ADHD has a range of aetiological origins which are associated with a number of disruptions in neuropsychological functioning. This study aims to examine how low birth weight, a proxy measure for a range of environmental complications during gestation, predicts ADHD symptom severity in preschool-aged children indirectly via neuropsychological functioning. Methods 197 preschool-aged children were recruited as part of a larger longitudinal study. Two neuropsychological factors were derived from NEPSY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
1
24
0
2
Order By: Relevance
“…Previous studies examining the association between LBW and ADHD have been inconsistent in controlling for prenatal substance use (Anderson et al, 2011; Botting et al, 1997; Class et al, 2014; Elgen, Sommerfelt, & Markestad, 2002; Elgen, Holsten, & Odberg, 2013; Hack et al, 2009; Halmoy, Klungsoyr, Skjaerven, & Haavik, 2012; Hatch, Healey, & Halperin, 2014; Szatmari et al, 1990). Additionally, more recent findings have indicated that prenatal tobacco exposure may not be causally associated with ADHD (D’Onofrio et al, 2008; Nigg & Breslau, 2007; Thapar et al, 2009), or may be predictive of comorbid externalizing spectrum psychopathology (i.e., ODD and CD), but not ADHD (Nigg & Breslau, 2007).…”
Section: Role Of Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining the association between LBW and ADHD have been inconsistent in controlling for prenatal substance use (Anderson et al, 2011; Botting et al, 1997; Class et al, 2014; Elgen, Sommerfelt, & Markestad, 2002; Elgen, Holsten, & Odberg, 2013; Hack et al, 2009; Halmoy, Klungsoyr, Skjaerven, & Haavik, 2012; Hatch, Healey, & Halperin, 2014; Szatmari et al, 1990). Additionally, more recent findings have indicated that prenatal tobacco exposure may not be causally associated with ADHD (D’Onofrio et al, 2008; Nigg & Breslau, 2007; Thapar et al, 2009), or may be predictive of comorbid externalizing spectrum psychopathology (i.e., ODD and CD), but not ADHD (Nigg & Breslau, 2007).…”
Section: Role Of Confounding Factorsmentioning
confidence: 99%
“…Further, parental age (both younger and older) has also been associated with increased risk for neurodevelopmental disorders, including ADHD (Gardener, Spiegelman, & Buka, 2009; Gustafsson & Kallen, 2011a). Parental age has also not been consistently covaried in studies investigating associations between LBW and ADHD (Anderson et al, 2011; Botting et al, 1997; Breslau et al, 1996; Elgen et al, 2002; Elgen et al, 2013; Hack et al, 2009; Hatch et al, 2014; Strang-Karlsson et al, 2008; Szatmari et al, 1990), and when parental age is used as a covariate, studies typically use maternal age, but not paternal age (Halmoy et al, 2012; Mick, Biederman, Prince, et al, 2002). …”
Section: Role Of Confounding Factorsmentioning
confidence: 99%
“…Thus, pre- and perinatal health may indirectly influence risk for ADHD and other disruptive behavior disorders, such that early insults influence the development of cortico-striatal circuitry, resulting in neuropsychological dysfunction and subsequently increasing liability for ADHD and/or other disruptive behavior problems. Hatch, Healey, and Halperin (2014) recently demonstrated that primary neuropsychological functioning (defined as visuo-spatial perception and motor coordination) mediated associations between birth weight and ADHD symptoms. However, while innovative, this work did not consider potential differential effects of pre- and perinatal health risk on ADHD versus disruptive behavior disorders (Nigg & Breslau, 2007), other potentially relevant indicators of risk (e.g., teratogen exposure, complications during pregnancy and/or delivery, perinatal health), or familial confounds (i.e., potential impact of shared genetic and environmental factors).…”
mentioning
confidence: 99%
“…Another study explains that birth weight has indirect effect on ADHD through primary neuropsychological functions. In fact, children with ADHD are more likely to have neuropsychological function problems, especially in children aged 3-4 years old (12).…”
Section: Resultsmentioning
confidence: 99%